Original paperStudy of relationship between IL-1Ra gene polymorphism and GVHD in HLA – identical sibling allogenic transplants - Nooridaloii, Mohammad Reza; Sobhani, Maryam; Izadi, Pantea; Fotouhi, Akbar; Moghadam, Kamran Ali; Iravani, Masoud; Jahani, Mohammad; Bahar, Babak; Moosavi, Asadollah; Hadiashar, Nima; Ghavamzadeh, Ardeshir (Archives of Medical Science, 2007)
Introduction: The interleukin-1 (IL-1) gene family includes three members (IL-1a, IL-1b and IL-1Ra) that mediate immune and inflammatory responses. Interleukin-1 (IL-1) is an inflammatory cytokine involved in various autoimmune and inflammatory diseases. IL-1 receptor antagonist (IL-1Ra) is the naturally occurring antagonist to IL-1a and IL-1b. A variable number tandem repeat (VNTR) polymorphism in the IL-1Ra gene has been associated with increased IL-1Ra production and affects the severity of aGVHD. Material and methods: Three hundred and fifty pairs (175 HSCT recipients and their donors) were analyzed by VNTR/PCR. Because of haematological disorders all patients were transplanted. All genotypes were screened blind to the clinical outcome of the transplants. GVHD was graded using Glucksberg criteria. Results: The influence of different alleles on incidence of aGVHD was investigated with univariate analysis. None of them showed an association with aGVHD, but possession of allele 2 in donors was associated with less severe aGVHD, although the frequency of allele 2 in our study population was low. However, aGVHD correlated with recipient age, donor age and recipient disease, particularly thalassaemia. Conclusions: No significant correlation was observed between the IL-1Ra polymorphism and incidence of aGVHD. In addition there was a powerful association between diagnosis, particularly thalassaemia, and GVHD (26 out of 30 thalassaemia patients). These findings may help to predict the risk/severity of GVHD, which may contribute to selecting strategies for treatment/prevention in thalassaemia patients.